1981
DOI: 10.1172/jci110313
|View full text |Cite
|
Sign up to set email alerts
|

Role of metabolic CO2 production in ventilatory response to steady-state exercise.

Abstract: A B S T R A C T We examined the role of metabolic CO2 production in the hyperpnea of muscular exercise by comparing the response of alveolar ventilation to moderate levels ofexercise with the response to venous infusion of CO2 at rest. Studies were performed in four awake sheep that were trained to run on a treadmill. The sheep had been cannulated for veno-venous extracorporeal perfusion so that CO2 could be infused into the peripheral venous blood through membrane lungs in the perfusion circuit. The sheep bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…Thus, under resting conditions, both loading and unloading venous CO 2 produce hypercapnic hyperpnea and hypocapnic hypopnea, respectively. Other studies have shown that the relationship of alveolar ventilation toV co 2 was the same in exercising sheep as during venous CO 2 loading, implying that the increase inV co 2 elicited by exercise can solely account for the ventilatory response, at least under these specific experimental conditions (419); this is consistent with the idea that nonmetabolic stimuli are not obligatory for the hyperpnea of mild-to-moderate levels of exercise.…”
Section: Feedback Influences Carbon Dioxide Flowsupporting
confidence: 81%
“…Thus, under resting conditions, both loading and unloading venous CO 2 produce hypercapnic hyperpnea and hypocapnic hypopnea, respectively. Other studies have shown that the relationship of alveolar ventilation toV co 2 was the same in exercising sheep as during venous CO 2 loading, implying that the increase inV co 2 elicited by exercise can solely account for the ventilatory response, at least under these specific experimental conditions (419); this is consistent with the idea that nonmetabolic stimuli are not obligatory for the hyperpnea of mild-to-moderate levels of exercise.…”
Section: Feedback Influences Carbon Dioxide Flowsupporting
confidence: 81%
“…Thus, the subjects were starved for at least 3 h before any measurements were made. Finally, there is some debate as to whether or not alterations in CO 2 elimination are accompanied by any change in arterial P CO 2 (Fordyce & Grodins, 1980;Phillipson et al 1981). Thus it seems quite unlikely that any residual differences in metabolic rate on different days could really explain the variations in P ET,CO 2 on different days in our subjects.…”
Section: A Crosby and P A Robbinsmentioning
confidence: 81%
“…These studies used an extracorporeal gas exchanger to increase or decrease venous and thus delivered CO 2 . In several studies on anesthetized animals, it was claimed thatV E changed in proportion to the change in CO 2 delivery to maintain homeostasis of PaCO 2 (206,214,274,314,338). In contrast, in an equal number of studies, there was a change in PaCO 2 sufficient to account for the hyperpnea or hypopnea during CO 2 loading and unloading (39,118,138,171,209,277,284,300).…”
Section: Venous Co 2 Content As a Signal For The Exercise Hyperpneamentioning
confidence: 99%